PENGEMBANGAN MODEL PEMBELAJARAN BAHASA INGGRIS BERBASIS PAIKEM DI KELAS EMPAT DI SDN 08/IV LUBUK GAUNG 1 MERANGIN TAHUN AJARAN 2024-2025 - EKI, A EKI KURNIAWAN SY (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Achievement of improved learning English at SDN 08/IV new mine is very low, for Factor that affect the quality of student learning in SDN 08/IV Lubuk Gaung 1 Merangin is only using one book and only use the question and answer method. So, students tend to feel tired and bored with the existing learning. Based on this background, research on the issue of whether to use the reading model that will be used to improve the quality of teaching and student learning, researchers are trying to develop a model with methods PAIKEM (Learning, Active, Innovative, Creative, Effective and Fun) at the fourth-grade students SDN 08/IV at Lubuk Gaung 1 Merangin in order to improve the quality English learning of the student. This type of research is the Research and Development with familiar woer R&D. In this case the researchers will develop a learning model that is able to improve the quality of student learning, with reading skills, reading skill very influential in improving English learning. This research also helps the teachers to improve their teaching during teaching and learning process. While the subject of this research is the fourth grade students of SDN 08/IV academic years 2013/2014 with a total of 13 people, consisting of 6 males students and 7 female students. The results of this research experienced a significant increase, starting from the results of the validation performed by 3 validator, the validation of learning model based on PAIKEM, lesson plan validation, medium of validation, each validator obtained range of scores > 25, therefore this model fit for use as an instructional material. After that the learning model used in the average values ​​obtained percentage of student learning activities in which they are granted model developed by the first and second meetings has increased, where student activity reached at the first meeting and the second meeting has the average value 80, 38.